2021
DOI: 10.1155/2021/9980949
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Multitarget Pharmacological Mechanism of Ursolic Acid Acting on Colon Cancer: A Network Pharmacology Approach

Abstract: Objective. To explore the mechanisms of ursolic acid for treating colon cancer based on network pharmacology. Method. In this study, the potential targets of ursolic acid against colon cancer were predicted and screened through the TCMSP, SYMMAP, Drug Bank, UNI-PROT, and DISGENET databases. The protein interaction (PPI) network was constructed based on the STRING database, and graphs were drawn with the help of Cytoscape software. GO and KEGG enrichment analyses were performed on the targets by using the DAVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Phytochemicals including UA may exert powerful efficacy against a variety of malignancies, such as CRC, gastric cancer, breast cancer, prostate cancer, , and lung cancer, with fewer adverse reactions in comparison with the compounds of chemotherapy, which gives rise to broad utilization of phytochemicals as nutraceuticals for intervention in various cancers. However, the action mechanisms for most phytochemicals remain to be clarified, and UA is one of them in great need of exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemicals including UA may exert powerful efficacy against a variety of malignancies, such as CRC, gastric cancer, breast cancer, prostate cancer, , and lung cancer, with fewer adverse reactions in comparison with the compounds of chemotherapy, which gives rise to broad utilization of phytochemicals as nutraceuticals for intervention in various cancers. However, the action mechanisms for most phytochemicals remain to be clarified, and UA is one of them in great need of exploration.…”
Section: Discussionmentioning
confidence: 99%
“…The action mode of multicomponent-multitarget-multipathway renders natural products better antitumor effects [ 90 ]. Apart from the aforementioned effects on immunosuppressive cells and immune effector cells, natural products can also modulate immune-related signaling pathways in glioma cells.…”
Section: Natural Products For Immunotherapy Of Gliomamentioning
confidence: 99%
“…For instance, pharmacological studies have suggested that the active components of Bupelum, ligusticum chuanxiong, andrographis, turmeric, and salvia miltiorrhiza are capable of regulating cancer, neurodegenerative diseases, and cardiovascular diseases through autophagy [ [6] , [7] , [8] , [9] , [10] ]. Moreover, Intervention with multiple components, multiple targets, and several ways is the material basis for TCM's effectiveness, with more complex biological function [ 11 ]. Accordingly, the research in this field has become a research hotspot.…”
Section: Introductionmentioning
confidence: 99%